The dispersal flight of Tribolium castaneum – A field test of laboratory generated predictions. (September 2019) - Gurdasani, Komal; Rafter, Michelle A.; Daglish, Gregory J.; Walter, Gimme H.
Abstract: The reasons for Tribolium castaneum undertaking dispersal flight in the field are poorly known. The research reported here was designed to test, in the field, the predictions generated from our previous laboratory study about the dispersal flight of T. castaneum beetles. The results of that laboratory study suggested that younger beetles with large bodies and higher fat content tend to fly more frequently, and female flyers are likely to live longer with a higher lifetime fecundity relative to those beetles that remain. These predictions were tested by sampling beetles flying within storage and at various distances (20 and 300 m) from a large population infesting stored cotton seed. Beetles were also collected directly from the infested cotton seed as a representation of 'resident beetles'. Of the adults collected, a subset was weighed and measured, and others were tested for their fecundity, fat content and lipofuscin levels. The survival and total fecundity of females (until day 105 post-emigration) was statistically similar across the treatments, but access to males later in life (i.e. after day 105), to a subset of females from each treatment, increased their fecundity (except for those trapped at 300 m). The majority of females that were caught dispersing are presumed to be relatively young, multiply mated, and produced numerous offspring (mean = 307.3) in the absence of males. Fat content was significantly higher across flying beetles (both sexes) trapped at 2 m (within the shed) compared to flying beetles trapped at longer distances. Flight propensity was evidently not influenced by sex, weight or body size. The lipofuscin intensities of flyers was generally significantly higher than those of resident males and females, although a reliable estimate of their age would add significant value to spatio-temporal studies in these beetles. These findings have implications for management of phosphine resistance. Graphical abstract: Image 10 Highlights: Tribolium castaneum in dispersal flight were physiologically characterised. Flight propensity was not related to sex, weight, fat content or size. All females in dispersal flight were highly fecund with a long life span. Estimated 1–4 fathers had sired the progeny of each female in dispersal flight. The study has implications for phosphine resistance management in the field.